PERTANGGUNGJAWABAN BPN TERHADAP HAK KEPEMILIKAN ATAS TANAH YANG DIBATALKAN (TINJAUAN PUTUSAN NO.132K/TUN/2010) - Novi Novi Novi (Ilmu Hukum Prima (IHP), 2018)
Land controversy that often occur has to do with legality or the proof of ownership, call it Certificate.Beside the problems that occur in the process of the administration of certificate issuance,the problems alsooccur at enforcement of judicial decisions, and the deed can be said to be an unlawful deedand of course is very harmful. A lot of judicial decisionsespecially stateadministrative court that already hasan absolute legal force. Which has not yet received a follow up action from National Land Agencybecause National Land Agency did not even did not firmly or negligent in performing their duties and liabilities in order to guarantee legal certainty and against their interestsIn reference to this research, writer refer to the legal norms contained in laws and regulations as well as the legal norms that exist in society. Writer collected data for this study byanalyzing from the books and records. Thus,the action that could be done to prevent the controversy of land rights certificate, as a matter of fact is that it could be done since the beginning, preventivelywhen applicating for rights administration on the land registration process. This preventive tactics are actually more effective compare tothe settlement of legal action effort if the controversy has already become a case.